Structural Basis for Polyproline-Mediated Ribosome Stalling and Rescue by the Translation Elongation Factor EF-P - Huter, Paul; Arenz, Stefan; Bock, Lars V; Graf, Michael; Frister, Jan Ole; Heuer, Andre; Peil, Lauri; Starosta, Agata L; Wohlgemuth, Ingo; Peske, Frank; Nováček, Jiří; Berninghausen, Otto; et al. (Molecular cell, 2017)
Ribosomes synthesizing proteins containing consecutive proline residues become stalled and require rescue via the action of uniquely modified translation elongation factors, EF-P in bacteria, or archaeal/eukaryotic a/eIF5A. To date, no structures exist of EF-P or eIF5A in complex with translating ribosomes stalled at polyproline stretches, and thus structural insight into how EF-P/eIF5A rescue these arrested ribosomes has been lacking. Here we present cryo-EM structures of ribosomes stalled on proline stretches, without and with modified EF-P. The structures suggest that the favored conformation of the polyproline-containing nascent chain is incompatible with the peptide exit tunnel of the ribosome and leads to destabilization of the peptidyl-tRNA. Binding of EF-P stabilizes the P-site tRNA, particularly via interactions between its modification and the CCA end, thereby enforcing an alternative conformation of the polyproline-containing nascent chain, which allows a favorable substrate geometry for peptide bond formation.
Keywords: EF-P; proteiny vázající RNA; proteiny z Escherichia coli; prolines; nascent chain; iniciační faktory; messenger RNA; translation elongation; RNA; simulace molekulového dockingu; RNA, Transfer; vztahy mezi strukturou a aktivitou; Structure-Activity Relationship; ribozomy; Protein Binding; Peptide Initiation Factors; ribosome; Peptide Elongation Factors; mutace; Molecular Docking Simulation; Protein Conformation; Eukaryotic Translation Initiation Factor 5A; Escherichia coli; vazebná místa; a-IF5A; Escherichia coli Proteins; Binding Sites; Ribosomes; peptidy; RNA transferová; Peptides; simulace molekulární dynamiky; elongační faktory; RNA, Messenger; proteosyntéza; single particle cryo-EM; eukaryotický translační iniciační faktor 5A; Molecular Dynamics Simulation; konformace nukleové kyseliny; vazba proteinů; Nucleic Acid Conformation; Mutation; Protein Biosynthesis; RNA-Binding Proteins; elektronová kryomikroskopie; eIF5A; stalling; Cryoelectron Microscopy; konformace proteinů